2015
DOI: 10.1109/jsen.2015.2404342
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Capacitive Tactile Sensors Based on Carbon Nanotube Thin Films

Abstract: Carbon nanotubes (CNTs) are an interesting material for mechanically flexible electronic devices. The possibility to fabricate CNT thin films from solution by scalable coating and printing techniques has paved the way for large-area and low-cost sensor applications. In this paper, we demonstrate mechanically flexible capacitive tactile sensors utilizing spray deposited CNT thin-films and microstructured PDMS spacers. The capacitance is monitored during sensor operation and forces smaller than 10 mN could be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 32 publications
(28 reference statements)
2
22
1
Order By: Relevance
“…As can be seen in Figure 5(b), the sensor goes back to its initial capacitance value if there is no force applied with an error less than 3% at the different force steps applied. If we compare this response with the one reported by Cagatay et al [25] for a PDMS film of about 110 m and pillar of about 30 m, we observe similar capacitance values under no force. The sensitivity is about 10% lower in the sensor described here, but the fabrication procedure and the integration on a final system are much easier.…”
Section: Capacitive Sensorssupporting
confidence: 83%
See 2 more Smart Citations
“…As can be seen in Figure 5(b), the sensor goes back to its initial capacitance value if there is no force applied with an error less than 3% at the different force steps applied. If we compare this response with the one reported by Cagatay et al [25] for a PDMS film of about 110 m and pillar of about 30 m, we observe similar capacitance values under no force. The sensitivity is about 10% lower in the sensor described here, but the fabrication procedure and the integration on a final system are much easier.…”
Section: Capacitive Sensorssupporting
confidence: 83%
“…The characterization of the force was performed as in [25]. A voice coil actuator VM2836-180 from Geeplus (Beckenham, UK) was used to generate the normal force .…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure sensor, monitoring the external force and deformation, has attracted people's attention in wearable devices and robotics. Generally, pressure sensors can detect the deformation and motions based on the piezoelectricity [1][2], capacitance [4][5][6][7][8] and resistance [9][10][11][12][13][14][15].The piezoelectric sensor shows high sensitivity and fast response time but are susceptible to external electric field and temperature. The capacitance-type sensor shows high sensitivity and has the potential in transparent pressure sensors while it is sensitive to strong electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms have been utilized to make pressure sensors such as resistive, 14,15 piezoresistive, 16 piezoelectric 17,18 and capacitive mechanisms. 19,20 The capacitive sensors have higher sensitivity and relatively simpler structures, and they can be integrated with other exible electronics or CMOS devices. Recent work has also demonstrated that a exible stress sensor array could have very high sensitivity in the small stress range from 0 to 30 kPa.…”
Section: Introductionmentioning
confidence: 99%